The Effect Of Work Discipline And Work Environment On Employee Performance At Pt. Crestec Indonesia, Bekasi District - Husnaedy, Kurniawan; Akbar, Irfan Rizka (International Journal of Social Sciences, 2025)
The research was conducted to determine the influence of work discipline and work environment on employee performance at PT CRESTEC INDONESIA, Bekasi Regency, both partially and simultaneously. The research method used is associative quantitative. The research sample consisted of 50 respondents obtained through a saturated sampling technique. The types of data used include primary and secondary data, with data collection techniques carried out through observation, interviews, questionnaires, and literature studies. The data analysis techniques used include data instrument testing, classical assumption testing, simple and multiple linear regression testing, correlation and determination coefficient testing, as well as partial and simultaneous hypothesis testing. The research results indicate that work discipline has a positive and significant effect on employee performance, with a significance value of 0.000<0.05 and a t-count value of 2.230>1.997 (t-table value). The work environment also has a positive and significant effect on employee performance, with a significance value of 0.000<0.05 and a t-count value of 5.609>1.997 (t-table value). Simultaneously, work discipline and work environment have a positive and significant effect on employee performance, with a significance value of 0.000<0.05 and an F-count value of 81.693>3.20 (F-table value). Work discipline and work environment also have a simultaneous determination level of 77.7%.